Catalytic Effect of A-Cyclodextrin on the Oxidation of Acetophenones Using N-Bromosaccharin as Oxidant in Aqueous Acetic Acid Medium - Radhakrishnan Nair, T.D.; Zachariah, Aleyamma (Asian Journal of Chemistry, 2010)
The kinetics of oxidation of acetophenone and substituted acetophenones by N-bromosaccharin has been investigated in aqueous acetic acid medium in the temperature range 308–323 K. The reaction is found to be first order with respect to acetophenone and zero order with respect to the reaction does not induce polymerisation of added acrylonitrile. A positive catalytic effect has been noticed on the addition of A-cyclodextrin. Thermodynamic parameters such as ΔS#,ΔH#, and ΔG# have been evaluated and presented.